Valuation of access to irrigation water in rural Ethiopia: application of choice experiment and contingent valuation methods - Mekonnen, A.; Gebreegziabher, Z.; Hagos, Fitsum (World Scientific Publishing, 2020)
Smallholder farmers in Africa rely heavily on rainfed agriculture. Those who have access to irrigation often receive it at no charge, but quantity, frequency and reliability may be limited without adequate revenue for maintenance and operation. Moreover, the absence of fees means that there are no pricing signals to encourage conservation of this scarce resource. In a situation where farmers do not pay for irrigation water use, this study investigates demand-side issues by eliciting farmers’ willingness to pay (WTP) for access to irrigation water. This study employs choice experiment (CE) and contingent valuation methods (CVMs) to value access to irrigation water, taking Ethiopia as a case in point. Unlike previous studies, this study covers current users and non-users of irrigation water using the same baseline (status quo) conditions — no irrigation — and compares the preferences of these two groups. The four attributes identified in the CE are number of crop seasons, frequency of watering in a season, crop type, and payment level. Results show that marginal WTP was Birr 17.7 (US$ 0.98), 261.8 (US$ 14.54) and 87.6 (US$ 4.87) for number of crop seasons, watering frequency in a season and crop type, respectively. Our estimates of farmers’ WTP for operation and maintenance of irrigation schemes per hectare of irrigated land range from Birr 738 (US$ 41.00) (from the CE) to Birr 784 (US$ 43.56) (from the CVM). We also find that, compared to current users, non-users were willing to pay more in general, as well as for the number of crop seasons specifically.